PEMBENTUKAN KARAKTER DISIPLIN SISWA MELALUI PENERAPAN TATA TERTIB SEKOLAH DAN PEMBELAJARAN PPKn DI SMA NEGERI 1 WAINGAPU - Arcella J.M.U Djoh; I Nengah Suastika; I Wayan Landrawan (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
The purpose of this study was to describe the formation of student discipline characters through the application of school discipline and Civics learning at SMA Negeri 1 Waingapu. This research is a descriptive qualitative research. This research was conducted at SMA Negeri 1 Waingapu. Data collection is done through interviews, observation, and documentation. The research data were analyzed by data collection, data reduction, data presentation, and conclusions. The results of this study are the formation of students' disciplined character through discipline starting from a). rules in school are made and formulated by students themselves, namely through the Student Council, the goal is to create disciplinary behavior in students without feeling burdened because disciplinary rules are the ideas of the students so that it arises awareness in students to obey the rules. b) the implementation of discipline in schools is carried out by all existing components, especially teachers and student councilors who routinely conduct raids on school attributes and other items that are prohibited at school. The formation of student discipline character through PPKn subjects, namely the teacher always emphasizes discipline in students, it starts from the teacher giving an example of discipline, creating a conducive learning atmosphere, and the teaching learning process is always orderly.